Direct numerical simulation of evaporating droplets based on a sharp-interface algebraic VOF approach - Shang, Xiaopeng (2022)
This study presents a sharp-interface algebraic volume-of-fluid (SA-VOF) approach towards direct numerical simulation of evaporating droplets in a finite-volume framework. An interface identification scheme is introduced to determine a sharp layer of interface cells where liquid-vapor phase change occurs. The rate of vaporization is directly computed from the local gradient of the vapor mass fraction at the interface without any tuning parameter in the evaporation model. In addition, a modified compressive differencing scheme is employed to maintain high resolution of the interface. A solver based on the SA-VOF approach is developed and validated by several case studies including the Stefan problem for evaporation in one dimension, evaporation of sessile droplets in the constant contact angle mode, and evaporation of droplets suspended in a flowing air stream. Comparisons between numerical predictions and either analytical solutions or experimental data show that the SA-VOF approach not only computes the evaporation rate with high accuracy but also ensures highly resolved liquid-vapor interface. The solver demonstrates the capability in revealing minute details of the complex characteristics associated with droplet evaporation.